Assessment of embodied carbon in timber and concrete building systems - Harrison, Dylan Thomas (Kansas State University, 2024)
This report analyzes and compares the embodied carbon impacts of timber and concrete structural systems through the cradle to gate phases of design and construction (A1-A5, Table 1). These phases are defined in the within the report. Furthermore, the report examines the industry’s current stance on sequestered carbon and reduction techniques. This report serves to establish a better understanding of the impacts that arise from unmanaged greenhouse gas emissions, as well as provide guidance on how to reduce the embodied carbon within a timber or concrete structural system. In the analysis, the superstructures were evaluated in two main phases (A1-A5, Table 1). The first phase, known as the product phase, included all processes necessary to ready the building materials for construction. The construction phase followed and included all operations needed to install the superstructure at the site. Using the information in this report, an embodied carbon estimating spreadsheet was created. This spreadsheet confines the information to a user-friendly platform capable of calculating embodied carbon quantities using inputs provided by the user. The information allows the user to pinpoint areas of concern within their design and compare them to alternative solutions. To compare the two building superstructures, a sample calculation was computed using assumed design criteria of a one-story building with a 20,000 ft2 footprint. The sample resulted embodied carbon masses of 73,294 kg for the timber system and 186,482 kg for the concrete system, yielding timber as the more carbon-efficient structural material for this building. To reduce embodied carbon within structural systems, carbon sequestration provides the greatest potential. Carbon sequestration is the process of capturing and storing carbon dioxide from the atmosphere. Although carbon sequestration has occurred naturally for many years, scientists and engineers are finding new ways to incorporate this concept. These methods can include bioengineering, as well as artificially placed carbon. With the continued advancement of sequestering techniques, the idea of carbon neutral building materials continues to grow in relevancy. The material analysis in this report includes a more detailed breakdown of embodied carbon within structural systems than the currently available estimating tool from the Structural Engineering Institute. The utilization of this report allows an industry professional to analyze where embodied carbon is sourced in their project and determine what alternatives would aid in reducing the carbon footprint. As the industry advances in sequestering technologies, the combination of reduction efforts will continue to increase its effectiveness over time.
Keywords: Embodied carbon; Timber systems; Concrete systems; Building; Emissions calculator